Assessment of Old Age Nutritional Status at Geriatric Home in Al- Diwaniyah City - Fatima R. Mohammed, Hala S. Abdulwahid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Because of the various harmful impacts of malnutrition on older individuals’ overall health, well-being, and autonomy, nutrition in the elderly has become a concern. Diet and lifestyle choices, as well as maintaining a healthy body weight, are important for maintaining health at any age, but they are especially important for healthy aging. Objective: Assess old age nutritional status throughout anthropometric measurements and MNA tool at Geriatric Home in AL-Diwaniyah City. Methodology: A cross-sectional study design utilizing the assessment approach is used to assess the nutritional status of the old ages in the Geriatric Home in AL-Diwaniyah City. Non-probability (convenient) sampling approach was used to select a sample of (24) old age live in Geriatric Home in AL-Diwaniyah City. These old age are distributed with respect to their age as early old age of (65-74) year, middle old age of (75-84) year and old-old age of (85 and more) year. Results: Findings demonstrated that the (45.8%) out of 24 participants from old age at geriatric home exhibited moderate nutritional status as described by moderate mean scores 29.08 (±6.128). Conclusion: Old ages who are unable to read and write is significantly associated with poor nutritional and those who are less years in geriatric home is significantly associated poor nutritional status. While those who are 9-21 kg/ m2 is significantly associated with poor nutritional status.